Experimental Testing of Natural Fiber on Asphalt Mix Performance - Alizar Alizar; Slamet Imam Wahyudi; Rachmat Mudiyono (Dinasti Research, 2024)
The performance of road pavements in Indonesia pays great attention to durability and high safety for users, considering the high rate of traffic growth every year. Utilizing natural fibers which are abundant in Indonesia in a hot mixed asphalt is one solution. This can be an alternative to asphalt content which will protect the pavement from damage, especially the surface layers which experiences collapse due to traffic loads and changes in temperature 20-50 °C. The characterization study of natural fiber in asphalt pavement is critical point for accurate fiber mixing to increase the performance of asphalt as a road surface layer. The objective of this study is evaluation the characterization and performance of three natural fibers namely coconut fiber, rice straw and palm fiber in mixtures of asphalt penetration 60/70. In this study, a mixture of asphalt with natural fibers were produced with a length variation of 2-5 mm. Diameter varied from 0.1-0.7 mm. The variation of fiber size was conducted to determine its effect on the asphalt characteristics. The addition of 0.1%, 0.2%, 0.3%, 0.4% and 0.5% fibers into asphalt pen 60/70 mixture changed the characteristics of the asphalt with wet process mixing 500 rpm in temperature 110oC. The results of characteristic test demonstrate that tensile strength of natural fibers 2.34 – 217.3 N/mm2. The asphalt concrete containing with 0.2% - 0.3% natural fibers showed value of Marshall Stability, Marshall Quotient and Marshall Immersion is significant in of performance asphalt concrete and this method can improve the quality of asphalt mixture.